The History of Taxes and Obligations In The Kokand Khanate - ug’li , Dusaliyev (Indonesian Journal Publisher, 2025)
As history teaches us, taxes have played a significant role in the political and economic life of all states. Even in today’s developed and advanced countries, tax policy remains one of the most sensitive issues. In this article, we discuss the history of taxes and obligations in the Kokand Khanate, which existed from 1709 to 1876. This study examines the taxation and obligations system in the Kokand Khanate, utilizing systematic, comparative, and statistical analyses to evaluate its evolution and impact. Historical sources and archival records reveal that taxation, such as the “zakat,” “kharja,” and “tanobona,” was vital for the khanate’s economic foundation, supporting governance, military expenditures, and infrastructure. However, the imposition of excessive taxes and unpaid labor obligations led to widespread discontent, culminating in social uprisings like the Polatkhan Rebellion. Findings highlight distinct approaches by rulers, such as Umar Khan’s reforms that strengthened trade and governance versus Khudoyar Khan’s oppressive tax policies, which exacerbated societal tensions. The study concludes that while taxation underpinned the khanate’s prosperity during certain periods, mismanagement and a lack of reform contributed significantly to its decline and eventual annexation by Tsarist Russia. These outcomes underscore the critical balance between state financial needs and societal well-being in maintaining political stability.